Increased spontaneous activity of the superior frontal gyrus with reduced functional connectivity to visual attention areas and cerebellum in male smokers - Niu, Xiaoyu; Gao, Xinyu; Lv, Qingqing; Zhang, Mengzhe; Dang, Jinghan; Sun, Jieping; Wang, Weijian; Wei, Yarui; Cheng, Jingliang; Han, Shaoqiang; Zhang, Yong (Frontiers in Human Neuroscience, 2023)
Background: Chronic smokers have abnormal spontaneous regional activity and disrupted functional connectivity as revealed by previous neuroimaging studies. Combining different dimensions of resting-state functional indicators may help us learn more about the neuropathological mechanisms of smoking. Methods: The amplitude of low frequency fluctuations (ALFF) of 86 male smokers and 56 male nonsmokers were first calculated. Brain regions that displayed significant differences in ALFF between two groups were selected as seeds for further functional connectivity analysis. Besides, we examined correlations between brain areas with abnormal activity and smoking measurements. Results: Increased ALFF in left superior frontal gyrus (SFG), left medial superior frontal gyrus (mSFG) and middle frontal gyrus (MFG) as well as decreased ALFF in right calcarine sulcus were observed in smokers compared with nonsmokers. In the seed-based functional connectivity analysis, smokers showed attenuated functional connectivity with left SFG in left precuneus, left fusiform gyrus, left lingual gyrus, left cerebellum 4 5 and cerebellum 6 as well as lower functional connectivity with left mSGF in left fusiform gyrus, left lingual gyrus, left parahippocampal gyrus (PHG), left calcarine sulcus, left cerebellum 4 5, cerebellum 6 and cerebellum 8 (GRF corrected, Pvoxel < 0.005, Pcluster < 0.05). Furthermore, attenuated functional connectivity with left mSGF in left lingual gyrus and PHG displayed a negative correlation with FTND scores (r = -0.308, p = 0.004; r = -0.326, p =0.002 Bonferroni corrected). Conclusions: Our findings of increased ALFF in SFG with reduced functional connectivity to visual attention areas and cerebellum subregions may shed new light on the pathophysiology of smoking. Keywords: amplitude of low-frequency fluctuation (ALFF), functional connectivity (FC), superior frontal gyrus, visual attention, cigarette smoking